Обгрунтування параметрів роботи вібраційного грунтообробного знаряддя для обробітку грунту - Кутковецька, Тетяна Олександрівна; Kutkovetska, Tetyana (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: В статті проведені дослідження щодо зменшення енерговитрат та підвищення якості обробітку грунту шляхом використання в грунтообробному знарядді робочих органів вібраційної дії з обгрунтуванням параметрів їх роботи. Наукову новизну становить установка додаткових елементів на стійках робочих органів, які будуть здійснювати їх коливальні рухи під час обробітку грунту і таким чином, краще його розпушувати. При цьому практична цінність полягає в тому, що вібраційне знаряддя дозволить зменшити тяговий опір та знизити енерговитрати до 20 % на виконання технологічної операції обробітку ґрунту. Отримані результати дослідження показали, що пропонована розробка, дозволить забезпечити якісні показники обробітку грунту, що відповідають агротехнічним вимогам. Крім того за результатами досліджень визначено, що конструктивне технічне рішення також забезпечить високу продуктивність роботи грунтообробного знаряддя вібраційної дії та може використовуватися для обробітку ґрунту на різних агрофонах при різній твердості ґрунту. /// EN: The article presents research on reducing energy consumption and improving the quality of soil cultivation by using vibrating working elements in soil cultivation implements with justification of their operating parameters. From the analysis of literary sources, it was found that existing vibration disruptors are classified into mechanical, electrical, hydraulic and pneumatic. One of the most promising areas of development and application of vibration sources for tillage tools is electrical exciters of mechanical vibrations, namely a solenoid with a metal core inside. Based on the analysis of existing technical means for soil cultivation, we propose a new technical means of vibration action for mound-free soil cultivation. The scientific novelty is the installation of additional elements on the racks of the working elements, which will perform their oscillatory movements during soil cultivation and thus better loosen it. A structural and technological scheme of a combined tillage implement with an electric vibration exciter and a device for automatic regulation of the technological process of the tillage machine have been developed. At the same time, the practical value lies in the fact that the vibrating tool will reduce traction resistance and reduce energy consumption by up to 20 % for performing the technological operation of soil cultivation. The obtained research results showed that the proposed development will ensure high-quality soil cultivation indicators that meet agrotechnical requirements. In addition, the results of the research determined that the proposed constructive technical solution will also ensure high performance of the soil tillage tool of vibration action and can be used for soil cultivation on different agro-backgrounds with different soil hardness.
Justification of the working parameters of a vibratory land cultivation tool for soil cultivation
Keywords: грунтообробне знаряддя; обробіток грунту; параметри роботи; робочі органи; вібраційна дія; тяговий опір; енерговитрати; технічне рішення; розпушування грунту; технологічна операція; tillage implement; soil cultivation; operating parameters; working bodies; vibration action; traction resistance; energy consumption; technical solution; loosening the soil; technological operation